APPLICATION OF K-MEANS METHOD IN THE SPREAD OF POSITIVE CASES OF COVID-19 IN SALATIGA CITY - Gladis Tri Enggiel; Hindriyanto Dwi Purnomo (Jurnal Teknik Informatika (Jutif), 2022)
Covid-19 is an infectious disease caused by SARS-CoV-2. It was discovered in Wuhan, China. It has been spread in every countries, especially in Indonesia. It has spreading all districts/cities in every province, one of it is City of Salatiga. This research used to determine the grouping of the spread of Covid-19 positive cases in each "kelurahan" in order to find out which villages has contributed the most positive cases. The research uses the calculation process for the distribution of clusters, it is divided into 3 which are categorized as overage (from the range 200-150), moderate (from the range 100-55), and few (from the range 50-5). This grouping process is assisted by the RapidMiner Studio tools. From this calculation, cluster 1 (C1 = a lot) is the highest cluster consisting of 5 villages, cluster 2 (C2 moderate) is a medium cluster consisting of 6 villages, and cluster 0 (C3 is few) is a small cluster. consists of 12 villages. From this grouping, it can be seen that cluster 1 is the highest cluster because the highest range is in cluster 1. The results of this grouping can be applied and can provide information about the spread of positive cases of Covid-19 in Salatiga City.